Combination therapy with alisertib enhances the anti-tumor immunity induced by a liver cancer vaccine - Fang Xue; Jing Liu; Jinyan Wu; Xueer Li; Ningning Zhu; Shuting Tang; Mengli Zhang; Huan Duan; Rui Wang; Jing Zhang (iScience)
Summary: Alisertib is a potent aurora A kinase inhibitor in clinical trials for cancer treatment, but its efficacy on cancer vaccines remains unclear. Here, we developed a DNA vaccine targeting glypican-3 (pGPC3) and evaluated its efficacy with alisertib in hepatocellular carcinoma (HCC) models. The combination therapy of pGPC3 vaccine and alisertib significantly inhibited subcutaneous tumor growth, enhanced the induction and maturation of CD11c+ and CD8+CD11c+ dendritic cells (DCs), and expanded tumor-specific CD8+ T cell responses. CD8+ T cell depletion abolished the anti-tumor effects, underscoring the essential role of functional CD8+ T cell responses. Moreover, the combined treatment promoted memory CD8+ T cell induction, providing long-term protection. In liver orthotopic tumor models, the combination of pGPC3 vaccine and alisertib demonstrated potent therapeutic efficacy through CD8+ T cell responses. These results indicate that alisertib enhances the pGPC3 vaccine’s therapeutic effect, offering a promising strategy for HCC treatment.